2014
DOI: 10.2204/iodp.proc.320321.218.2014
|View full text |Cite
|
Sign up to set email alerts
|

Data report: late Miocene to early Pliocene coccolithophore and foraminiferal preservation at Site U1338 from scanning electron microscopy

Abstract: The late Miocene to early Pliocene carbonate-rich sediments recovered at Integrated Ocean Drilling Program (IODP) Site U1338 during the Expedition 320/321 Pacific Equatorial Age Transect (PEAT) program contain abundant calcareous nanno- and microfossils. Geochemical proxies from benthic and planktonic foraminiferal and coccolithophore calcite could be very useful at this location; however, good preservation of the calcite is crucial for the proxies to be robust. Here, we evaluate the preservation of specific b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…We reconstructed vertical water mass structure and biogenic bloom extent by integrating the new Site U1338 planktic δ 13 C data with fine fraction (<63 μm) (Reghellin et al, ) and benthic δ 13 C records (Drury et al, ). At Site U1338, the <63 μm fine fraction contains a large calcite component, which predominantly consists of coccolithophore calcite and some foraminiferal fragments (Drury et al, ; Reghellin et al, ), as observed elsewhere in the eastern equatorial Pacific (Broecker & Clark, ; Shackleton & Hall, ). Foraminiferal and coccolithophore δ 13 C values predominantly reflect the δ 13 C of the dissolved inorganic carbon (δ 13 C DIC ) in the surrounding seawater (Epstein et al, ; Kroopnick, ; Margolis et al, ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We reconstructed vertical water mass structure and biogenic bloom extent by integrating the new Site U1338 planktic δ 13 C data with fine fraction (<63 μm) (Reghellin et al, ) and benthic δ 13 C records (Drury et al, ). At Site U1338, the <63 μm fine fraction contains a large calcite component, which predominantly consists of coccolithophore calcite and some foraminiferal fragments (Drury et al, ; Reghellin et al, ), as observed elsewhere in the eastern equatorial Pacific (Broecker & Clark, ; Shackleton & Hall, ). Foraminiferal and coccolithophore δ 13 C values predominantly reflect the δ 13 C of the dissolved inorganic carbon (δ 13 C DIC ) in the surrounding seawater (Epstein et al, ; Kroopnick, ; Margolis et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…To circumvent unknown changes in past δ 18 O sw , we use the relationship of ~−0.23‰/°C (slope of foraminiferal δ 18 O‐ T relationship derived by Epstein et al, ), to provide a first‐order approximation of relative temperature change based on the planktic δ 18 O record (Figure b, right axis). Selecting visually well‐preserved T. sacculifer minimized the effect of diagenesis on the planktic δ 18 O record, supported by scanning electron microscopy on T. sacculifer from Site U1338 showing that inorganic calcite overgrowths and infilling are absent, and that original growth features are retained (Drury et al, ). Although palaeo‐vital effects remain difficult to constrain (Birch et al, ; Nathan & Leckie, ), by selecting T. sacculifer from a narrow and consistent size fraction at Site U1338, vital effects relating to ontogenic changes likely remained comparable throughout the record.…”
Section: Discussionmentioning
confidence: 94%
“…The EDS maps of (b and c) views 2 and 3 are presented in this study, the EDS maps of (a and d) views 1 and 4 were first presented in Drury et al . [].…”
Section: Resultsmentioning
confidence: 99%
“…The late Miocene to early Pliocene interval is well documented at this location by published alkenone‐derived ( U37k') SST, benthic, bulk, and 2–5 μm fraction δ 18 O records [ Rousselle et al ., ; Drury et al ., ]. Furthermore, scanning electron microscopy (SEM) studies show that coccoliths dominate the <63 μm fine fraction, although some etching removed central heterococcolith features and small amounts of secondary overgrowth are reported [ Drury et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…The weight percent CaCO 3 is ~70–80%, decreasing to ~40–60% in discrete intervals [ Lyle et al , ; Lyle and Backman , ]. Benthic foraminifera are well preserved, with evidence of only minor calcite overgrowth and dissolution [ Drury et al , ].…”
Section: Methodsmentioning
confidence: 99%